Emerging challenges in the health systems of Kerala, India: qualitative analysis of literature reviews - Manesh Muraleedharan; Alaka Omprakash Chandak (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The substantial increase in non-communicable diseases (NCDs) is considered a major threat to developing countries. According to various international organizations and researchers, Kerala is reputed to have the best health system in India. However, many economists and health-care experts have discussed the risks embedded in the asymmetrical developmental pattern of the state, considering its high health-care and human development index and low economic growth. This study, a scoping review, aims to explore four major health economic issues related to the Kerala health system. Design/methodology/approach - A systematic review of the literature was performed using PRISMA to facilitate selection, sampling and analysis. Qualitative data were collected for thematic content analysis. Findings - Chronic diseases in a significant proportion of the population, low compliance with emergency medical systems, high health-care costs and poor health insurance coverage were observed in the Kerala community. Research limitations/implications - The present study was undertaken to determine the scope for future research on Kerala's health system. Based on the study findings, a structured health economic survey is being conducted and is scheduled to be completed by 2021. In addition, the scope for future research on Kerala's health system includes: (1) research on pathways to address root causes of NCDs in the state, (2) determine socio-economic and health system factors that shape health-seeking behavior of the Kerala community, (3) evaluation of regional differences in health system performance within the state, (4) causes of high out-of-pocket expenditure within the state. Originality/value - Given the internationally recognized standard of Kerala's vital statistics and health system, this review paper highlights some of the challenges encountered to elicit future research that contributes to the continuous development of health systems in Kerala.